Up-Conversion Photoluminescence in Polyfluorene Doped with Metal(II)-Octaethyl Porphyrins - Keivanidis, Panagiotis E.; Baluschev, Stanislav; Miteva, Tzenka; Nelles, Gabriele; Scherf, Ullrich; Yasuda, Akio; Wegner, Gerhard (My University, 2003)
The quasi-continuous wave (cw) up-conversion in polyfluorenes (PF) films doped with metal (II)-octaethyl porphyrins was studied. An intercavity frequency-doubled diode-pumped cw-Nd:YAG laser and the green line of a helium-neon laser were used as pumping sources. The efficiency of the up-conversion process in poly(9,9-bis(2-ethylhexyl)fluorene):Pd(2,7,8,12,13,17,18-octaethyl-porphyri nato) (PF2/6:PdOEP) was estimated by direct excitation of the active host polymer by pumping at 405 nm. The results show that the pump intensities were five orders of magnitude lower than the pump intensities used.
Keywords: Absorption; Continuous wave lasers; Density (optical); Doping (additives); Fluorescence; Gas lasers; Liquid crystals; Molecular vibrations; Morphology; Neodymium lasers